Self-efficacy level to recover from addiction in substance users in the center for Drug Rehabilitation - Supriyanto, Agus; Hendiani, Nurlita (Universitas PGRI Madiun, 2018)
Self-efficacy is a predictor for individuals with Substance Abuse Disorders (SAD) to recover from drug addiction. The need for measurements to determine the efficacy of individuals with SAD. The aim of the study was to determine the level of self-efficacy of people with SAD to recover from drug addiction in the level dimensions, strength dimensions, and general dimensions. This study uses a descriptive approach. The research instrument was self-efficacy scale with subject N = 217. Research subjects were substance users undergoing a drug rehabilitation program at the Drug Rehabilitation Center, Indonesia. Research subjects had 217 with male gender (Re-entry, HOC, Faith, Care, and Hope) and female gender (Female). Quantitative descriptive analysis to determine the level of self-efficacy in individuals with SAD. The level dimension at a high level. Unlike the level dimension, that in the dimension of individual strength and individual generality to recover has a low level. Level dimension differences with the dimensions of strength and general dimensions because the level dimension is limited to individual feelings to be able to recover from drug addiction, while the dimensions of strength and general center on cognitive, affective, and psychomotor aspects to recover from drug addiction. Counselors can design a counseling strategy to develop self-efficacy and prevent relapse.